The Role of Islamic Da'wah in Preventing Violence and Building Harmonious Families - Hajar, Aprilita (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2025)
A strong family is the foundation of a harmonious and prosperous society. However, the increasing cases of domestic violence indicate ongoing problems in family dynamics, which may be influenced by the imbalance of education between husband and wife. Such disparities can lead to misunderstandings and conflicts that threaten household harmony. This study aims to explore the role of Islamic da'wah in preventing domestic violence by promoting balanced education and strengthening awareness of the rights and responsibilities between spouses. Using a qualitative approach through a literature review of key Islamic sources—such as Qur’anic interpretation (tafsir), hadith, and works of contemporary Muslim scholars—this research highlights the moral and ethical teachings of Islam on compassion, justice, and mutual responsibility in family life. The findings show that Islamic da'wah that emphasizes understanding of balanced education, respectful communication, and the internalization of Islamic values can significantly contribute to reducing the potential for domestic violence and fostering harmonious families. Unlike previous studies that focused primarily on doctrinal aspects, this study offers a novel perspective by emphasizing the transformative role of da'wah in promoting educational equality within the family. Thus, reinforcing Islamic da'wah becomes a strategic step in addressing the complexity of modern family challenges.